PENGARUH OPINI AUDIT, AUDIT DEELAY, DAN AUDIT FEE TERHADAP AUDITOR SWITHCING DENGAN FINANCIAL DISTRESS SEBAGAI VARIABEL MODERASI - Dian Murdianingsih; Jayanti, Esti (Fakultas Ekonomi dan Bisnis Universitas Pekalongan, 2025)
This study aims to analyze the effect of Audit Opinion, Audit Delay, and Audit Fee on Auditor Switching with Financial Distress as a moderating variable in State-Owned Enterprises for the period 20202024. The analytical tool used is SPSS 16 software. The results of the study indicate that Audit Opinion, Audit Delay, and Audit Fee have a significant influence on Auditor Switching. Financial Distress is able to moderate the influence of Audit Opinion and Audit Fee on Auditor Switching. However, financial distress is unable to moderate the influence of Audit Delay on Auditor Switching.